A cerium-zirconium solid solution with adjustable particle size and preparation method thereof

By controlling the heating time of zirconium salt solution and the concentration of zirconium solution and regulating the particle size of cerium-zirconium solid solution, the problem of difficult particle size regulation in the existing process is solved, and efficient particle size regulation and production efficiency are achieved.

CN118416876BActive Publication Date: 2025-02-14JIANGMEN KANHOO IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410366530.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2025-02-14
Estimated Expiration
2044-03-28

AI Technical Summary

Technical Problem

The existing cerium-zirconium solid solution preparation process cannot effectively regulate the particle size, resulting in particle size deviation and low production efficiency.

Method used

By controlling the heating time of the zirconium salt solution and the concentration of the starting zirconium solution, the particle size of the cerium-zirconium solid solution is adjusted to achieve the adjustability of the particle size.

Benefits of technology

It realizes precise regulation of the particle size of cerium-zirconium solid solution, improves production efficiency, and meets industrial applications with different particle size requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004764396790000101
    Figure BDA0004764396790000101
  • Figure BDA0004764396790000111
    Figure BDA0004764396790000111
  • Figure BDA0004764396790000121
    Figure BDA0004764396790000121
Patent Text Reader

Abstract

The invention belongs to the field of catalysts, and discloses a method for preparing a cerium-zirconium solid solution with adjustable particle size, comprising the following steps: step 1: pre-mixing a soluble sulfate and a soluble zirconium salt solution to obtain a zirconium salt solution, and heating the solution to 95-100°C; step 2: heat-keeping and aging the solution of step 1 to obtain a zirconium precursor slurry; step 3: mixing the zirconium precursor slurry, a soluble rare earth metal salt, and a soluble cerium salt to obtain a salt solution; step 4: mixing the salt solution and hydrogen peroxide, adding an alkaline substance to adjust the pH to obtain a precipitate; step 5: filtering and roasting the precipitate to obtain a cerium-zirconium solid solution. The present invention is characterized in that: the concentration of zirconium ions in the zirconium salt solution is controlled to be 5-6wt%, and the heating time before the zirconium salt solution reaches 95-100°C is controlled to be 10-80min; compared with the general sulfate coordination coprecipitation method, the present invention can accurately control the particle size of the cerium-zirconium solid solution to obtain products with different particle size requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a cerium-zirconium solid solution with adjustable particle size and a preparation method thereof. Background Art

[0002] At present, the three-way catalytic converter (TWC) is a device that controls the CO, HC and NO produced by incomplete combustion in the automobile combustion chamber. x The main technology to eliminate HC / CO / NO x The conversion is strongly affected by the oxygen partial pressure, so Ce-Zr composite oxides with catalytic release or oxygen adsorption properties have been widely used in TWCs. Cerium is considered to be the main oxygen storage material because Ce 4+ / Ce 3+ The reversible transformation of CeO 2 The ability to store and release oxygen under oxygen-deficient and oxygen-rich conditions, the so-called oxygen storage capacity (OSC), and the ability to stably disperse precious metals on its surface to increase the thermal stability of the catalyst. 2 Compared with CeO 2 -ZrO 2 The solid solution has good thermal stability, excellent oxygen mobility and a large number of oxygen vacancies, which are the key factors for the development of ternary catalysts with high temperature stability and low temperature activity. 3+ , La 3+ , Nd 3+ and Pr 3+ ), which can further increase the oxygen vacancies in the fluorite lattice, perform charge compensation, promote the diffusion or transfer of oxygen, and improve the thermal stability and oxygen storage and release capacity of the solid solution.

[0003] The sulfate coordination co-precipitation method uses sulfate to coordinate with zirconium ions to form a complex, and then uses sodium hydroxide as a precipitant to precipitate and transform zirconium and rare earth elements to obtain a porous hydroxide precursor, which is then calcined to obtain the product. However, the current traditional cerium-zirconium solid solution preparation process is unable to limit or regulate the particle size of the prepared cerium-zirconium solid solution, resulting in large particle size deviations in products of the same preparation process at different times. In response to different particle size requirements, most of the large-particle oxygen storage materials are re-crushed and ball-milled to meet the processing requirements of smaller-particle materials. Since the re-crushing and ball-milling process consumes a lot of time and labor costs, and the instability of the particle size also leads to different control parameters of the post-processing process, it greatly affects the production efficiency and economic benefits of the entire preparation process.

[0004] In the prior art, CN 117509725 A discloses a cerium-zirconium solid solution with an ultrafine grain size, the purpose of which is to improve the specific surface area and particle size of the cerium-zirconium solid solution after aging, comprising step 1: mixing basic zirconium sulfate, a soluble rare earth metal salt, and a soluble cerium salt to obtain a salt solution; step 2: mixing hydrogen peroxide and the salt solution, and adjusting the pH to obtain a precipitate; step 3: washing and roasting the precipitate to obtain a cerium-zirconium solid solution;

[0005] CN 112573569 B discloses a rare earth composite oxide with high heat resistance and a preparation method thereof. By adjusting the amount of sulfate added and the amount of structure regulator added, the pore size distribution of the material can be controlled to meet different application requirements. The rare earth composite oxide of the invention has a particle size of 10-20 μm and a specific surface area of ​​85-100 m 2 / g; after aging at 1000℃ for 4h, the specific surface area is 55-70m 2 / g; after aging at 1100℃ for 4h, the specific surface area is 30-40m 2 / g.

[0006] In actual industrial applications, cerium-zirconium oxygen storage materials are mostly processed by re-crushing and ball-milling large-particle oxygen storage materials to meet the processing requirements of smaller-particle materials. For this reason, materials with smaller initial particle sizes will greatly limit their applicability in industrial production, and the re-crushing and ball-milling process is also extremely time-consuming, which greatly affects the production efficiency and economic benefits of the entire preparation process.

[0007] After further research on the prior application CN 117509725 A, the applicant found that it is difficult to achieve adjustable particle size below 20 μm based on this solution. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a cerium-zirconium solid solution with adjustable particle size. The particle size of the cerium-zirconium solid solution can be controlled by controlling the heating time of the zirconium salt solution. Within the selected initial zirconium solution concentration range, the particle size regulation effect shows a "parabolic" trend change. At the same time, the present invention ensures the high activity of the cerium-zirconium solid solution.

[0009] At the same time, the present invention also provides a cerium-zirconium solid solution prepared based on the method.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] A method for preparing a cerium-zirconium solid solution with adjustable particle size, characterized in that it comprises the following steps:

[0012] Step 1: premixing a soluble sulfate and a soluble zirconium salt solution to obtain a zirconium salt solution, and heating the solution to 95-100° C.;

[0013] Step 2: heat-curing the solution of step 1 to obtain a zirconium precursor slurry;

[0014] Step 3: mixing a zirconium precursor slurry, a soluble rare earth metal salt, and a soluble cerium salt to obtain a salt solution;

[0015] Step 4: Mix the salt solution and hydrogen peroxide, and add alkaline substances to adjust the pH to obtain precipitation;

[0016] Step 5: filtering and calcining the precipitate to obtain a cerium-zirconium solid solution;

[0017] The concentration of zirconium ions in the zirconium salt solution is 5-6wt%;

[0018] The heating time of step 1 is 10-80 minutes.

[0019] The zirconium precursor slurry (also called "basic zirconium sulfate slurry") plays the role of "skeleton"; after reacting with alkali solution, the structure of basic zirconium sulfate remains basically unchanged during the transformation to hydroxide, and other metal ions can precipitate and grow on its framework. Therefore, the particle size of the precipitated precursor does not change much before and after the alkali reaction. Multiple cerium-zirconium precursors prepared by the same preparation method in the same period will be calcined under the same conditions, and the final particle size of the obtained cerium-zirconium solid solution will be reduced due to high-temperature dehydration, but the particle size change law is basically consistent with the precursor. Therefore, the particle size of the stabilized basic zirconium sulfate basically determines the final particle size of the cerium-zirconium solid solution.

[0020] By changing the concentration and heating time of the starting Zr solution, it is ultimately to change the solute concentration and heating rate in the solution, and this change will cause the time the solution is in the nucleation stage to be changed, resulting in an increase or decrease in the number of nuclei, but the content of Zr ions in the system is fixed, so the Zr ions used in the nuclear growth stage become less or more, causing the particle size of the prepared basic zirconium sulfate to change and affecting the final particle size of the cerium-zirconium solid solution.

[0021] To achieve controllable particle size (or controllable nucleation number), the concentration of zirconium ions should be controlled within an appropriate range. If the concentration is below or above the range, the adjustability of the particle size will be significantly deteriorated.

[0022] In some preferred cases of the present invention, the concentration of zirconium ions in the zirconium salt solution is 5.0wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, and 6.0wt%.

[0023] In the above method, in step 2, a soluble sulfate solution is added for heat preservation and aging; the molar ratio of the soluble sulfate to the soluble zirconium salt in step 2 is 0.2-0.4:1;

[0024] And / or, in step 1, the molar ratio of soluble sulfate to soluble solution is 0.2-0.4:1;

[0025] And / or, the aging time in step 2 is 0-75 min.

[0026] First, add a small amount of sulfate to the zirconium salt solution. After heating to above 95°C and keeping warm for a period of time, the solution system will enter the nucleation stage, and basic zirconium sulfate will exist in the solution in the form of small crystal nuclei. Then continue to add sulfate solution to the basic zirconium sulfate sol. The sulfate will combine with the free zirconium ions in the solution and accumulate on the surface of the crystal nucleus to form particles. With the disordered accumulation and growth between the particles, a basic zirconium sulfate precursor with a macroporous structure is formed. The rare earth composite oxide prepared using this basic zirconium sulfate precursor with a macroporous structure in the subsequent process also has a macroporous structure.

[0027] In some preferred cases of the present invention, the molar ratio of the soluble sulfate to the soluble zirconium salt in step 2 is 0.2:1, 0.22:1, 0.24:1, 0.26:1, 0.28:1, 0.3:1, 0.32:1, 0.34:1, 0.36:1, 0.38:1 or 0.4:1;

[0028] In some preferred cases of the present invention, in step 1, the molar ratio of the soluble sulfate to the soluble zirconium salt is 0.2:1, 0.22:1, 0.24:1, 0.26:1, 0.28:1, 0.3:1, 0.32:1, 0.34:1, 0.36:1, 0.38:1 or 0.4:1.

[0029] In the above method, in step 1, the soluble zirconium salt is any one or more combinations of zirconium oxychloride and zirconium nitrate.

[0030] In the above method, in step 3, the soluble rare earth metal salt is any one or more combinations of chloride salts and nitrate salts.

[0031] In the above method, in step 3, the mixing temperature is 20-60°C.

[0032] In some preferred cases of the present invention, the mixing temperature in step 3 is 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C.

[0033] In the above method, in step 4, hydrogen peroxide and Ce 3+The molar ratio is 0.5-2:1.

[0034] By moving the addition time of hydrogen peroxide to before the coprecipitation reaction, the hydrogen peroxide and the metal ions in the solution are fully mixed, and Ce 3+ With H 2 O 2 The reaction generates cerium peroxide, a transition state species, which allows Ce 3+ The precipitation pH and precipitation time were greatly advanced, making Ce 3+ It can precipitate with Zr ions under similar pH conditions, which greatly improves the problem of uneven precipitation of cerium-zirconium solid solution and low solid solubility. Since hydrogen peroxide is more active in extremely acidic and alkaline environments, the metal ions in the solution can precipitate in a high-valent state, forming a highly active and high-solubility cerium-zirconium solid solution.

[0035] In the above method, in step 4, the alkaline substance is any one or more combinations of sodium hydroxide and potassium hydroxide, and the pH is adjusted to 11.5-12 by the above method.

[0036] In the above method, the cerium-zirconium solid solution includes the following components in weight percentage: 30-60% zirconium dioxide, 24-65% cerium dioxide, and 5-16% oxides of other rare earth metals except cerium.

[0037] In the above method, the oxide of other rare earth metals other than cerium includes at least one of yttrium oxide, lanthanum oxide, praseodymium oxide and neodymium oxide.

[0038] In the above method, in step 5, the calcination temperature is 700-900°C;

[0039] And / or, in step 5, after filtering, a filter residue is obtained, the filter residue is washed and redispersed in a solvent, a structure regulator is added to obtain a slurry, and the slurry is filtered, dried and calcined to obtain a cerium-zirconium solid solution;

[0040] More specifically, after washing the filter residue, it is redispersed in a solvent, and then a structure regulator is added at 25-70° C. and stirring is continued for 30-60 minutes to obtain a slurry;

[0041] The solvent is at least one of water and ethanol;

[0042] The structure regulator is at least one of β-diketone compounds, fatty amines, and fatty acids; the β-diketone compound is at least one of stearylbenzoylmethane, ethyl acetylacetonate, 4,6-dioxoheptanoic acid, di-tert-valerylmethane, 2,4-octanedione, and dibenzoylmethane; the fatty acid is at least one of octanoic acid, nonanoic acid, capric acid, dodecanoic acid, octadecanoic acid, oleic acid, and citric acid; the fatty amine is at least one of dodecylamine, oleylamine, trioctyldecyl tertiary amine, n-caprylamine, tetramethylammonium hydroxide, and hexadecyltrimethylammonium hydroxide; and the structure regulator accounts for 20-50% of the weight of the porous rare earth composite oxide.

[0043] A cerium-zirconium solid solution is prepared by the method.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The present invention finds that by controlling the concentration of the initial zirconium solution and the heating time, the final particle size of basic zirconium sulfate and the solid solution can be regulated;

[0046] 2. The preparation method of the present invention can achieve a final particle size D50 of cerium-zirconium solid solution between 3-15 μm, and a specific surface area of ​​fresh samples of 60-80 m 2 / g, and the specific surface area after aging at 1100℃ / 10h is greater than 25m 2 / g, and still maintain high activity. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] Part 1 Particle size variation trend at initial zirconium ion concentration of 5wt%

[0049] Embodiment 11

[0050] A cerium-zirconium composite oxide comprises the following components in percentage by weight: 50% zirconium oxide, 40% cerium oxide, 4% lanthanum oxide, 2% yttrium oxide and 4% neodymium oxide.

[0051] The specific preparation method is:

[0052] (1) preparing a zirconium oxychloride solution with a zirconium ion concentration of 5 wt% in advance, adding a portion of sodium sulfate to obtain a zirconium solution;

[0053] The molar ratio of sodium sulfate to zirconium oxychloride is 0.2:1.

[0054] (2) The external oil temperature of the reactor is set to 120° C., and the zirconium solution is stirred and heated to 98° C. The time for heating to 98° C. is 40-50 minutes.

[0055] (3) After the mixture was heated to 98° C. under stirring, a 15 wt % sodium sulfate solution was added, wherein the molar ratio of sodium sulfate to zirconium oxychloride was 0.4:1, and the mixture was stirred at 98° C. for 20 min to obtain a zirconium precursor slurry.

[0056] (4) After the zirconium precursor slurry is cooled to 40°C, cerium chloride, lanthanum chloride, yttrium chloride, and neodymium chloride solutions are added, and at the same time, 27.5wt% hydrogen peroxide is poured in, wherein the hydrogen peroxide and Ce 3+ The molar ratio is 1:1 and stir thoroughly.

[0057] (5) A sodium hydroxide solution with a concentration of 10 wt % was prepared in advance and added dropwise to the mixed solution at a uniform rate until the pH value of the slurry reached 11.5, thereby obtaining a cerium-zirconium composite hydroxide precipitate.

[0058] (6) Filter the cerium-zirconium composite hydroxide and wash it with deionized water until the filter cake is neutral, treat it with a structure regulator, and then filter it. Then, calcine the cerium-zirconium composite hydroxide filter cake at 700° C. for 4 hours to obtain a porous cerium-zirconium composite oxide. Finally, use a pulverizer to crush the rare earth composite oxide to obtain a powder.

[0059] Example 12

[0060] The only difference from Example 11 is that the external oil temperature of the reactor is set to 140° C., and the time for heating the zirconium solution to 98° C. is controlled between 10 and 20 minutes.

[0061] Example 13

[0062] The only difference from Example 11 is that the time for heating the zirconium solution to 98° C. is controlled between 50 and 60 minutes.

[0063] Embodiment 14

[0064] The only difference from Example 11 is that the time for heating the zirconium solution to 98° C. is controlled between 70 and 80 minutes.

[0065] Embodiment 15

[0066] The only difference from Example 11 is that the time for heating the zirconium solution to 98° C. is controlled between 30 and 40 minutes.

[0067] Example 16

[0068] A cerium-zirconium composite oxide comprises the following components in weight percentage: 60% zirconium oxide, 24% cerium oxide and 16% lanthanum oxide.

[0069] The specific preparation method is:

[0070] (1) preparing a zirconium nitrate solution with a zirconium ion concentration of 5 wt% in advance, adding a portion of potassium sulfate to obtain a zirconium solution;

[0071] The molar ratio of potassium sulfate to zirconium nitrate is 0.4:1.

[0072] (2) The external oil temperature of the reactor is set to 120° C., and the zirconium solution is stirred and heated to 98° C. The time for heating to 98° C. is 40-50 minutes.

[0073] (3) After the mixture was heated to 98° C. under stirring, a 15 wt % potassium sulfate solution was added, wherein the molar ratio of potassium sulfate to zirconium nitrate was 0.3:1, and the mixture was stirred at 98° C. for 10 min to obtain a zirconium precursor slurry.

[0074] (4) After the zirconium precursor slurry is cooled to 60°C, cerium chloride and lanthanum chloride solutions are added, and at the same time, 27.5wt% hydrogen peroxide is poured in, wherein the hydrogen peroxide and Ce 3+ The molar ratio is 2:1 and stir thoroughly.

[0075] (5) A potassium hydroxide solution with a concentration of 10 wt % was prepared in advance and added dropwise to the mixed solution at a uniform rate until the pH value of the slurry reached 12, thereby obtaining a cerium-zirconium composite hydroxide precipitate.

[0076] (6) Filter the cerium-zirconium composite hydroxide and wash it with deionized water until the filter cake is neutral, treat it with a structure regulator, and then filter it. Then, calcine the cerium-zirconium composite hydroxide filter cake at 900° C. for 3 hours to obtain a porous cerium-zirconium composite oxide. Finally, use a pulverizer to crush the rare earth composite oxide to obtain a powder.

[0077] Embodiment 17

[0078] A cerium-zirconium composite oxide comprises the following components in percentage by weight: 30% zirconium oxide, 65% cerium oxide, 2% yttrium oxide and 3% praseodymium oxide.

[0079] The specific preparation method is:

[0080] (1) preparing a zirconium nitrate solution with a zirconium ion concentration of 5 wt% in advance, adding a portion of sodium sulfate to obtain a zirconium solution;

[0081] The molar ratio of sodium sulfate to zirconium nitrate is 0.3:1.

[0082] (2) The external oil temperature of the reactor is set to 120° C., and the zirconium solution is stirred and heated to 98° C. The time for heating to 98° C. is 40-50 minutes.

[0083] (3) After the mixture was heated to 98° C. under stirring, a 15 wt % sodium sulfate solution was added, wherein the molar ratio of sodium sulfate to zirconium nitrate was 0.4:1, and the mixture was stirred at 98° C. for 75 min to obtain a zirconium precursor slurry.

[0084] (4) After the zirconium precursor slurry is cooled to 50°C, cerium nitrate, yttrium nitrate, and praseodymium nitrate are added, and at the same time, hydrogen peroxide with a concentration of 27.5wt% is poured in. The hydrogen peroxide and Ce 3+ The molar ratio is 0.5:1 and stir thoroughly.

[0085] (5) A sodium hydroxide solution with a concentration of 10 wt % was prepared in advance and added dropwise to the mixed solution at a uniform rate until the pH value of the slurry reached 11.5, thereby obtaining a cerium-zirconium composite hydroxide precipitate.

[0086] (6) Filter the cerium-zirconium composite hydroxide and wash it with deionized water until the filter cake is neutral, treat it with a structure regulator and then filter it. Then, calcine the cerium-zirconium composite hydroxide filter cake at 800° C. for 6 hours to obtain a porous cerium-zirconium composite oxide. Finally, use a pulverizer to crush the rare earth composite oxide to obtain a powder.

[0087] Performance Testing

[0088] 1. D50 particle size test: tested using OMEC LS-POP(9) laser particle size analyzer;

[0089] 2. Specific surface area test: Micrometrics TriStar II 3020 fully automatic multi-station specific surface area pore analyzer is used for testing;

[0090] The specific surface area of ​​fresh samples represents the specific surface area of ​​the tested product in its fresh state after roasting and crushing;

[0091] 1100℃ / 10h specific surface area refers to the specific surface area of ​​the tested product after aging at 1100℃ for 10h;

[0092] The test results of the first part refer to Table 1;

[0093] Table 1 Test results when the initial zirconium ion concentration is 5wt%

[0094]

[0095]

[0096] In Examples 11-15, when the initial zirconium ion concentration is 5 wt%, the time for heating the zirconium solution to 98°C is controlled between 10 and 80 min. From the test results in Table 1, it can be seen that the final particle size D50 of the cerium-zirconium solid solution is 7.68 μm-14.06 μm, and the adjustable range of the final particle size of the cerium-zirconium solid solution is 6.38 μm.

[0097] Part 2 Particle size variation trend with initial zirconium ion concentration of 5.5wt%

[0098] Embodiment 21

[0099] The process is substantially the same as Example 11, except that the zirconium ion concentration of the pre-prepared zirconium oxychloride is 5.5 wt %, and the temperature of step 2 is 95° C.

[0100] Embodiment 22

[0101] The method is substantially the same as Example 21, except that the time for heating the zirconium solution to 95° C. is controlled between 10 and 20 minutes.

[0102] Embodiment 23

[0103] The method is substantially the same as Example 21, except that the time for heating the zirconium solution to 95° C. is controlled between 30 and 40 minutes.

[0104] Embodiment 24

[0105] The method is substantially the same as Example 21, except that the time for heating the zirconium solution to 95° C. is controlled between 50 and 60 minutes.

[0106] Embodiment 25

[0107] The method is substantially the same as Example 21, except that the time for heating the zirconium solution to 95° C. is controlled between 70 and 80 minutes.

[0108] The test method of the second part refers to the first part, and the test results refer to Table 2;

[0109] Table 2 Test results when the initial zirconium ion concentration is 5.5wt%

[0110]

[0111]

[0112] In Examples 21-25, when the initial zirconium ion concentration is 5.5wt%, the time for heating the zirconium solution to 95°C is controlled between 10 and 80min. From the test results in Table 2, it can be seen that the final particle size D50 of the cerium-zirconium solid solution is 7.12μm-13.25μm, and the adjustable range of the final particle size of the cerium-zirconium solid solution is 6.13μm, with a large adjustable range of particle size.

[0113] Part 3 Particle size variation trend at initial zirconium ion concentration of 6wt%

[0114] Embodiment 31

[0115] The process is substantially the same as Example 11, except that: a zirconium oxychloride solution having a zirconium ion concentration of 6 wt% is prepared in advance, and the temperature of step 2 is controlled at 99°C to 100°C.

[0116] Embodiment 32

[0117] The method is substantially the same as Example 31, except that the time for heating the zirconium solution to 99°C to 100°C is controlled between 10 and 20 minutes.

[0118] Embodiment 33

[0119] The method is substantially the same as Example 31, except that the time for heating the zirconium solution to 99°C to 100°C is controlled between 30 and 40 minutes.

[0120] Embodiment 34

[0121] The method is substantially the same as Example 31, except that the time for heating the zirconium solution to 99°C to 100°C is controlled between 50 and 60 minutes.

[0122] Embodiment 35

[0123] The method is substantially the same as Example 31, except that the time for heating the zirconium solution to 99°C to 100°C is controlled between 70 and 80 minutes.

[0124] The test method of Part 3 refers to Part 1, and the test results refer to Table 3;

[0125] Table 3 Test results when the initial zirconium ion concentration is 6wt%

[0126]

[0127] In Examples 31-35, when the initial zirconium ion concentration is 6 wt%, the time for heating the zirconium solution to 99°C-100°C is controlled between 10 and 80 min. From the test results in Table 3, it can be seen that the final particle size D50 of the cerium-zirconium solid solution is 3.17 μm-12.88 μm, and the adjustable range of the final particle size of the cerium-zirconium solid solution is 9.71 μm, with a large adjustable range of particle size.

[0128] Part 4 Particle size variation trend when the initial zirconium ion concentration is 4.5wt%

[0129] Embodiment 41

[0130] It is substantially the same as Example 11, except that a zirconium oxychloride solution having a zirconium ion concentration of 4.5 wt % is prepared in advance.

[0131] Embodiment 42

[0132] The method is substantially the same as Example 41, except that the time for heating the zirconium solution to 98°C is controlled between 10 and 20 minutes.

[0133] Embodiment 43

[0134] The method is substantially the same as Example 41, except that the time for heating the zirconium solution to 98°C is controlled between 30 and 40 minutes.

[0135] Embodiment 44

[0136] The method is substantially the same as Example 41, except that the time for heating the zirconium solution to 98°C is controlled between 50 and 60 minutes.

[0137] Embodiment 45

[0138] The method is substantially the same as Example 41, except that the time for heating the zirconium solution to 98°C is controlled between 70 and 80 minutes.

[0139] The test method of Part 4 refers to Part 1, and the test results refer to Table 4;

[0140] Table 4 Test results when the initial zirconium ion concentration is 4.5wt%

[0141]

[0142] In Examples 41-45, when the initial zirconium ion concentration is 4.5wt%, the time for heating the zirconium solution to 98°C is controlled between 10 and 80 minutes. From the test results in Table 4, it can be seen that the final particle size D50 of the cerium-zirconium solid solution is 10.73μm-14.54μm, and the adjustable range of the final particle size of the cerium-zirconium solid solution is 3.8μm, and the adjustable range of the particle size is very small.

[0143] Part 5 Particle size variation trend when the initial zirconium ion concentration is 6.5wt%

[0144] Embodiment 51

[0145] It is substantially the same as Example 11, except that a zirconium oxychloride solution having a zirconium ion concentration of 6.5 wt % is prepared in advance.

[0146] Embodiment 52

[0147] The method is substantially the same as Example 51, except that the time for heating the zirconium solution to 98°C is controlled between 10 and 20 minutes.

[0148] Embodiment 53

[0149] The method is substantially the same as Example 51, except that the time for heating the zirconium solution to 98°C is controlled between 30 and 40 minutes.

[0150] Embodiment 54

[0151] The method is substantially the same as Example 51, except that the time for heating the zirconium solution to 98°C is controlled between 50 and 60 minutes.

[0152] Embodiment 55

[0153] The method is substantially the same as Example 51, except that the time for heating the zirconium solution to 98°C is controlled between 70 and 80 minutes.

[0154] The test method of Part 5 refers to Part 1, and the test results refer to Table 5;

[0155] Table 5 Test results when the initial zirconium ion concentration is 6.5wt%

[0156]

[0157]

[0158] In Examples 51-55, when the initial zirconium ion concentration is 6.5wt%, the time for heating the zirconium solution to 98°C is controlled between 10 and 80 minutes. From the test results in Table 5, it can be seen that the fluctuation of the particle size in Examples 51 and 53-55 is very small, and the final particle size D50 of the cerium-zirconium solid solution is 6.27μm-11.51μm. The adjustable range of the final particle size of the cerium-zirconium solid solution is 5.2μm, and the adjustable range of the particle size is relatively small.

[0159] Result analysis:

[0160] 1. It can be seen from the test results in Tables 1 to 3 that when the initial concentration of zirconium ions in the soluble zirconium salt is 5wt% to 6wt%, the particle size of basic zirconium sulfate can be well controlled by adjusting the heating time, thereby achieving the adjustment of the solid solution particle size;

[0161] 2. It can be seen from Tables 4 and 5 that when the initial concentration of zirconium ions in the soluble zirconium salt is lower than 5wt% or higher than 6wt%, the particle size and solid solution particle size of basic zirconium sulfate cannot be significantly regulated by adjusting the heating time.

[0162] The core of the present invention is: by controlling the concentration of the initial zirconium solution, the oil temperature and the heating time, the particle size of the basic zirconium sulfate is regulated, so as to achieve the purpose of accurately regulating the final particle size of the cerium-zirconium solid solution. Since it is an optimization and improvement based on the previous advantageous preparation process, while ensuring the high activity of the cerium-zirconium solid solution, it meets the requirements of the product supply and demand sides for different particle sizes. The cerium-zirconium solid solution obtained by the preparation method of the present invention can be simply crushed to obtain a powder of the expected particle size, which greatly saves production time and cost, while ensuring its good applicability in industrial production. Therefore, the preparation method of the present invention has great application potential in actual industrial production.

[0163] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, and it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a cerium-zirconium solid solution with adjustable particle size, characterized in that: The steps include: Step 1: premixing a soluble sulfate and a soluble zirconium salt solution to obtain a zirconium salt solution, and heating the solution to 95-100° C.; Step 2: heat-curing the solution of step 1 to obtain a zirconium precursor slurry; Step 3: mixing a zirconium precursor slurry, a soluble rare earth metal salt, and a soluble cerium salt to obtain a salt solution; Step 4: Mix the salt solution and hydrogen peroxide, and add alkaline substances to adjust the pH to obtain precipitation; Step 5: filtering and calcining the precipitate to obtain a cerium-zirconium solid solution; The concentration of zirconium ions in the zirconium salt solution is 5-6wt%; The heating time of step 1 is 10-80min; In step 1, the molar ratio of the soluble sulfate to the soluble zirconium salt solution is 0.2-0.4: 1; In the step 2, a soluble sulfate solution is added for heat preservation and aging, and the molar ratio of the added soluble sulfate to the soluble zirconium salt is 0.2-0.4: 1; The heat preservation and aging time in step 2 is 0-75min; In step 4, hydrogen peroxide and Ce 3+ The molar ratio is 0.5-2:

1.

2. The method for preparing a cerium-zirconium solid solution according to claim 1, characterized in that: The soluble sulfate in step 1 is any one or more combinations of sodium sulfate and potassium sulfate, and the soluble zirconium salt is any one or more combinations of zirconium oxychloride and zirconium nitrate.

3. The method for preparing a cerium-zirconium solid solution according to claim 1, characterized in that: In step 3, the soluble rare earth metal salt is any one or more combinations of chloride salts and nitrate salts; And / or, in step 3, the mixing temperature is 20-60°C.

4. The method for preparing a cerium-zirconium solid solution according to claim 1, characterized in that: In the step 5, the calcination temperature is 700-900°C; And / or, in step 5, after filtering, filter residue is obtained, the filter residue is washed and redispersed in a solvent, a structure regulator is added to obtain slurry, and the slurry is filtered, dried and calcined to obtain a cerium-zirconium solid solution.

5. The method for preparing the cerium-zirconium solid solution according to claim 1, characterized in that: In the step 4, the alkaline substance is any one or more combinations of sodium hydroxide and potassium hydroxide. In the step 4, the pH is adjusted to 11.5-12.

6. The method for preparing a cerium-zirconium solid solution according to claim 1, characterized in that: The cerium-zirconium solid solution comprises the following components in weight percentage: 30-60% zirconium dioxide, 24-65% cerium dioxide, and 5-16% oxides of other rare earth metals except cerium.

7. The method for preparing a cerium-zirconium solid solution according to claim 6, characterized in that: The oxide of other rare earth metals other than cerium includes at least one of yttrium oxide, lanthanum oxide, praseodymium oxide and neodymium oxide.

8. A cerium-zirconium solid solution, characterized in that: The method is prepared by any one of claims 1 to 7.

Citation Information

Patent Citations

  • A rare earth composite oxide with high heat resistance and its preparation method

    CN112573569B

  • Preparation method of easy-to-form nano composite zirconium oxide powder

    CN113929137A

  • Cerium-zirconium solid solution with ultrafine grain size and preparation method thereof

    CN117509725A